2020
DOI: 10.1002/bies.202000094
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐Adrenergic Blockers as a Potential Treatment for COVID‐19 Patients

Abstract: More than 15 million people have been affected by coronavirus disease 2019 (COVID-19) and it has caused 640 016 deaths as of July 26, 2020. Currently, no effective treatment option is available for COVID-19 patients. Though many drugs have been proposed, none of them has shown particular efficacy in clinical trials. In this article, the relationship between the Adrenergic system and the renin-angiotensin-aldosterone system (RAAS) is focused in COVID-19 and a vicious circle consisting of the Adrenergic system-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 75 publications
(104 reference statements)
1
57
1
4
Order By: Relevance
“…This correlates with our previous genomic analysis on the UK Biobank COVID-19 cohort, which identified genes associated with some of these complications, including host pathogenic responses, inflammatory cytokine production, modulation of cardiac function and endothelial cell function 20. Use of medications such as proton pump inhibitors, dihydropyridines and beta-adrenergic blockers were observed in seven disease signatures in Cohort 1 and 80 signatures in Cohort 2. Dihydropyridines 33,34 and beta-adrenergic blockers 35,36 have been associated with improved outcomes for COVID-19 patients and suggested as potential treatments, while proton pump inhibitors have been associated with adverse outcomes in several studies 37,38 . The incidence of the medications in the disease signatures could be either due to adverse effects cause by the medication resulting in more severe COVID-19 response or it could reflect the comorbidities in patients for which they are generally prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…This correlates with our previous genomic analysis on the UK Biobank COVID-19 cohort, which identified genes associated with some of these complications, including host pathogenic responses, inflammatory cytokine production, modulation of cardiac function and endothelial cell function 20. Use of medications such as proton pump inhibitors, dihydropyridines and beta-adrenergic blockers were observed in seven disease signatures in Cohort 1 and 80 signatures in Cohort 2. Dihydropyridines 33,34 and beta-adrenergic blockers 35,36 have been associated with improved outcomes for COVID-19 patients and suggested as potential treatments, while proton pump inhibitors have been associated with adverse outcomes in several studies 37,38 . The incidence of the medications in the disease signatures could be either due to adverse effects cause by the medication resulting in more severe COVID-19 response or it could reflect the comorbidities in patients for which they are generally prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…A previous metaanalysis also showed that ACEIs/ARBs may have a protective effect in patients with community-acquired pneumonia and may reduce pneumonia-related mortality compared with that observed for the control group (30). Of note, losartan has been shown to ameliorate lung injury caused by SARS-CoV in an experimental study (40,41). Therefore, losartan may be a possible treatment method for reducing acute cardiopulmonary injury that can be applied in the clinic immediately (40,41).…”
Section: Therapeutic Strategies For Heart Failure In Covid-19 Patientsmentioning
confidence: 97%
“…Of note, losartan has been shown to ameliorate lung injury caused by SARS-CoV in an experimental study (40,41). Therefore, losartan may be a possible treatment method for reducing acute cardiopulmonary injury that can be applied in the clinic immediately (40,41). Unfortunately, the effects of ACEIs/ARBs in the treatment of patients with heart failure during COVID-19 have yet to be established.…”
Section: Therapeutic Strategies For Heart Failure In Covid-19 Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The author had recently proposed that adrenergic hyperactivation may explain all the complications occurring in the COVID-19 condition. [23] Recently alpha1 adrenergic blockers and beta-adrenergic blockers have been proposed to treat COVID-19 patients. [24,25] This evidence supports the claim that alpha1 and betaadrenergic blockers can be used in the COVID-19 patients to prevent adrenergic storm and thereby reverse the Warburg effect.…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%